Queer (dis)orientation in Oscar Wilde's "The Portrait of Mr W.H." (1889) - Hueso-Vasallo, Manuel (My University, 2021)
Following Sara Ahmed’s conceptualisation of queer phenomenology, this paper addresses how a relatively lesser-known short story by Oscar Wilde, “The Portrait of Mr W.H.” (1889) can be read as an orientation device towards the different artistic discourses of the past that inform queer culture and historiography. In the story, a cast of unreliable characters become obsessed with a forgery that attempts to pass as the original portrait of Shakespeare’s muse: Mr W.H. By positing this portrait as a point of historic and artistic conflict, the narrative turns its back to heteronormative realities and (dis)orientates both the characters and the readers, creating a queer effect.
Keywords: Teoría queer; Wilde, Oscar (1854-1900) - Crítica e interpretación; Homosexualidad en la literatura; Oscar Wilde; Sara Ahmed; Orientation